Clays and Clay Minerals, Vol. 60, No. 2, 108–120, 2012. - Jeong, Sueng Won; Locat, Jacques; Leroueil, Serge (The Clay Minerals Society, 2012)
Particle-particle interactions in natural clays can be evaluated by their rheological behavior, but the results are often affected by the physicochemical properties of the clays. The behaviors of two fundamentally different types of clays (low-activity and high-activity) differ with respect to salinity and a time factor (duration of shearing at a given shear rate): illite-rich Jonquiere clay (low-activity clay, Canada) and montmorillonite-rich Wyoming bentonite (high-activity clay, USA). The purpose of the present study was to investigate these different behaviors. Most natural clays exhibit shear-thinning and thixotropic behavior with respect to salinity and the volumetric concentration of the solids. Natural clays also exhibit time-dependent non-Newtonian behavior. In terms of index value and shear strength, lowactivity and high-activity clays are known to exhibit contrasting responses to salinity. The geotechnical and rheological characteristics as a function of salinity and the shearing time for the given materials are compared here. The clay minerals were compared to estimate the inherent shear strengths, such as remolded shear strength (which is similar to the yield strength). Low-activity clay exhibits thixotropic behavior in a time-dependent manner. High-activity clay is also thixotropic for a short period of shearing, although rare cases of rheopectic behavior have been measured for long periods of shearing at high shear rates. The change from thixotropic to rheopectic behavior by bentonite clay has little effect at low shearing speeds, but appears to have a significant effect at higher speeds.
The Effects Of Salinity And Shear History On The Rheological Characteristics Of Illite-rich And Na-montmorillonite-rich Clays
gsccm60202-jeo.pdf -- 3,975KB
Keywords: Periodicals; Geology; Low-activity Clay; High-activity Clay; Salinity; Rheopectic; Thixotropic; Yield Strength